Functional insulator scanning of CpG islands to identify regulatory regions of promoters using CRISPR - Grob,A; Marbiah,MM; Isalan,M (Methods in Molecular Biology, 2018)
The ability to mutate a promoter in situ is potentially a very useful approach for gaining insights into endogenous gene regulation mechanisms. The advent of CRISPR/Cas systems has provided simple, efficient, and targeted genetic manipulation in eukaryotes, which can be applied to studying genome structure and function.The basic CRISPR toolkit comprises an endonuclease, Cas9, and a short DNA-targeting sequence, made up of a single guide RNA (sgRNA). The catalytic domains of Cas9 are rendered active upon dimerization of Cas9 with sgRNA, resulting in targeted double stranded DNA breaks. Among other applications, this method of DNA cleavage can be coupled to endogenous homology-directed repair (HDR) mechanisms for the generation of site-specific editing or knockin mutations, at both promoter regulatory and gene coding sequences.A well-characterized regulatory feature of promoter regions is the high abundance of CpGs. These CpG islands tend to be unmethylated, ensuring a euchromatic environment that promotes gene transcription. Here, we demonstrate CRISPR-mediated editing of two CpG islands located within the promoter region of the MDR1 gene (Multi Drug Resistance 1). Cas9 is used to generate double stranded breaks across multiple target sites, which are then repaired while inserting the beta globin (β-globin) insulator, 5′HS5. Thus, we are screening through promoter regulatory sequences with a chromatin barrier element to identify functional regions via “insulator scanning.” Transcriptional and functional assessment of MDR1 expression provides evidence of genome engineering. Overall, this method allows the scanning of CpG islands to identify their promoter functions.